Changes in oxidation-reduction potential (ORP) during microbial transformation processes in bulk water phase under anoxic condition / Muhamad Sahrizan Sepiai - Sepiai, Muhamad Sahrizan (2006)
The sewer is a reactor for chemical and microbial transformations of wastewater. These in-sewer processes affect the quality of the wastewater and thereby the sewer itself, the subsequent treatment and the receiving water quality. Thesis focuses on the changes in oxidation-reduction potential (ORP) during microbial transformation processes in bulk water phase under anoxic condition. This study is based on experimental works on microbial transformation processes in the bulkwater phase of municipal wastewater. Test on 7 different municipal wastewater samples taken from the inlet of wastewater treatment plant (WWTP) at IWK Section 23, Shah Alam were conducted. In this study, a reactor subjected to anoxic condition was used to measure the ORP value and to determine the nitrate/nitrite utilization rate (NUR) during the anoxic condition. The sample that extracted from reactor was tested for nitrate and nitrite concentration by ion chromatography unit Metrohm and I.C 790 respectively.